Consumer Preference Analysis of Turmeric Simplisia Attributes Using the Conjoint Analysis Method at PT CAN Herbs Indonesia - Anugerah Putri Unikinova; Fitria Naimatus Sadiyah; Adi Prayoga (PAKIS JOURNAL INSTITUTE, 2026)
Indonesia has substantial potential for the development of biopharmaceutical crops, including turmeric (Curcuma domestica Val.), which is widely used as a raw material in the herbal industry. However, the declining demand for dried turmeric simplicia indicates a mismatch between the characteristics of the products offered and consumer preferences. This study aimed to analyze consumer preferences for dried turmeric simplicia attributes using conjoint analysis. The study was conducted using a full-profile approach by distributing questionnaires to 40 respondents, consisting of home industry business actors, micro, small, and medium enterprises (MSMEs), and herbal industries. The analyzed attributes included price, moisture content, payment system, and color. The data were analyzed to obtain the utility value and relative importance of each attribute. The results showed that price was the most influential attribute in consumer decision-making, followed by payment system, moisture content, and color. The most preferred attribute combination was dried turmeric simplicia with a moisture content of <8%, a price of IDR 35,000.00-40,000.00, full upfront payment, and bright yellow color. Consumer preferences for dried turmeric simplicia were multidimensional and influenced by a combination of product attributes. Therefore, producers are advised to implement quality standardization and competitive pricing strategies to improve the market competitiveness of dried turmeric simplicia.